Molecular Characterization of Propionibacterium acnes Isolated from Acne vulgaris - Polugari, Roselin; Marla, Shailaja Raj; Shailaja, D. (Innovations in Microbiology and Biotechnology Vol. 3, 2022)
Propionibacterium acnes is the most common member of the Anaerobic or microaerophilic coryneform organisms found on the skin. The present study focused on the isolation of Propionibacterium acnes, the causative organism of acne and its characterization based on the cultural characteristics, biochemical tests, GC FAME (Gas Chromatography- Fatty acid methyl esters) analysis and 16 S r RNA sequencing. The results were compared with the standard organisms procured from IMTECH, Chandigarh, India. The FAME analysis report of the organism correlates with that of the genotyping of the isolate and the organism is identified as Propionibacterium acnes. Study Objectives: To isolate acne causing organism using different media. To identify the organism based on conventional methods- cultural characterization and Molecular characterization.